2017
DOI: 10.1093/jee/tox044
|View full text |Cite
|
Sign up to set email alerts
|

Cypermethrin Formulation (Ustad-10 EC) Induces Genotoxicity via Apoptosis, Affects Nutritional Physiology, and Modulates Immune Response in Silkworm Philosamia ricini (Lepidoptera: Saturniidae)

Abstract: Cypermethrin is a pyrethroid insecticide with high insecticidal activity, low mammalian toxicity, and biodegradability. The present study aimed to determine the acute toxicity and evaluate the secondary toxic effects of a commercial formulation of cypermethrin on silkworm Philosamia ricini Hutt of Northeast India. The potential genotoxicity of cypermethrin on silkworm hemocyte was examined by comet assay, caspase activation, and annexin V affinity assay. Alteration in nutritional physiology and histoarchitectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…These results are important because of the paucity of information on invertebrate immunity and atrazine. While the effects of atrazine on vertebrate immunity have received a great deal of attention ( Rohr and McCoy 2010 , Sifkarovski et al 2014 ) and several authors have documented effects of other agrochemicals on invertebrate immune systems ( Chen et al 2017 , Kalita et al 2017 , Zhu et al 2017 ), we did not find studies examining the impact of atrazine on invertebrate immune systems, despite the high levels of use in the United States ( Atwood and Paisley-Jones 2017 ).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These results are important because of the paucity of information on invertebrate immunity and atrazine. While the effects of atrazine on vertebrate immunity have received a great deal of attention ( Rohr and McCoy 2010 , Sifkarovski et al 2014 ) and several authors have documented effects of other agrochemicals on invertebrate immune systems ( Chen et al 2017 , Kalita et al 2017 , Zhu et al 2017 ), we did not find studies examining the impact of atrazine on invertebrate immune systems, despite the high levels of use in the United States ( Atwood and Paisley-Jones 2017 ).…”
Section: Discussionmentioning
confidence: 62%
“…Immune stress from environmental contaminants is likely to place additional strain on this cost/benefit system ( Guedes et al 2016 ). A number of authors have documented the impact of pesticides on economically important terrestrial species ( Chen et al 2017 , Kalita et al 2017 , Zhu et al 2017 ). However, fewer studies have focused on immunological impacts of pesticides on nontarget insect species, particularly in the aquatic environment.…”
mentioning
confidence: 99%
“…Haemocytes are considered to have a significant part in maintaining the cellular and humoral immune system in insects (Kalita and Devi, 2016). Others (Kalita et al, 2017;Kalita and Devi, 2016) suggested that haemocytes viability can be modulated either by targeting constituents of insect immune systems or by regulating immune responses. Such alterations negatively influence the hematopoietic system along with the aberration in endocrine gland activity (Feroz, 2020).…”
Section: Mechanism For Insecticidal Activitymentioning
confidence: 99%
“…Alternatively, the observed effects may be due to an indirect effect of the insecticide on mosquito physiology and immunity. Insecticides can affect insect immunity in several ways (reviewed in [55]), including effects on the number of hemocytes [56], on the activity of immune enzymes [57,58], on the melanisation and antibacterial responses [5] and on oxidative stress. Indeed, pyrethroid insecticides are a major source of reactive oxygen species (ROS) in exposed organisms [3,4,59], and ROS are a common immune defense against many pathogens [60], including Plasmodium [61][62][63].…”
Section: Infection Prevalence and Intensitymentioning
confidence: 99%